2021
DOI: 10.1186/s13054-021-03785-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of zinc sulfate as an adjunctive therapy in COVID-19 critically ill patients: a two center propensity-score matched study

Abstract: Background Zinc is a trace element that plays a role in stimulating innate and acquired immunity. The role of zinc in critically ill patients with COVID-19 remains unclear. This study aims to evaluate the efficacy and safety of zinc sulfate as adjunctive therapy in critically ill patients with COVID-19. Methods Patients aged ≥ 18 years with COVID-19 who were admitted to the intensive care unit (ICU) in two tertiary hospitals in Saudi Arabia were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…However, stage 2-3 AKI patients represented more severe clinical cases, and it is possible that this population may not benefit from zinc supplementation. A recent study of critically ill patients in the ICU with COVID-19, however, showed an association of oral zinc supplementation with reduced AKI incidence ( 33 ). An exact mechanism for a renal protective effect of zinc has not been identified, but zinc may mitigate AKI risk through antioxidant action ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, stage 2-3 AKI patients represented more severe clinical cases, and it is possible that this population may not benefit from zinc supplementation. A recent study of critically ill patients in the ICU with COVID-19, however, showed an association of oral zinc supplementation with reduced AKI incidence ( 33 ). An exact mechanism for a renal protective effect of zinc has not been identified, but zinc may mitigate AKI risk through antioxidant action ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in line with data from other studies, where zinc was administered together with other substances and synergistic effects were observed as well. [35][36][37] It has for example been observed that zinc can augment effects of other drugs, trace elements, and vitamins such as vitamin D3 as well as it may reduce the dosage necessary to reach optimal effects. [35][36][37] This was demonstrated here especially for the sensitive PMN, while higher concentrations may be necessary to affect GM-CSFR-induced signaling in monocytes and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth article shows findings on the association between Zn and the survival of hospitalized patients with COVID-19 [ 178 ]. The sixth paper presents results of a retrospective case series study on the treatment of COVID-19 outpatients with Zn in combination with low-dose HCQ and AZM [ 179 ] and another two studies provide data on the efficacy and safety of Zn as adjunctive therapy in critically ill patients with COVID-19 [ 180 ] as well as the effectiveness of this element in the prevention and mitigation of COVID-19 [ 181 ]. Finally, the last multi-center cohort study shows data on the effect of Zn with a ionophore on COVID-19 in-hospital mortality rates [ 182 ].…”
Section: Covid-19: Elementsmentioning
confidence: 99%
“…The sixth study with 141 COVID-19 patients (median age 58 y) receiving Zn, HCQ, and AZM (i.e., Zn sulfate: 220 mg, 50 mg elemental Zn, once daily; HCQ: 220 mg twice daily; AZM: 500 mg once daily) for five consecutive days demonstrated that the treatment with the triple therapy may prevent a large number of hospitalizations [ 179 ]. One of three last studies—i.e., a two-center retrospective study [ 180 ] on 164 patients aged ≥ 18 y (82 receiving Zn at a daily dose of 220 mg, 50 mg elemental Zn)—indicated that Zn, as an additional treatment, may have survival benefits. Other interventional, prospective, single-blind study [ 181 ] involving 96 control subjects (71 y of age) and 104 patients (74 y of age) treated with 10, 25, or 50 mg of Zn picolinate daily revealed that the Zn supplementation in all three doses may be effective prophylaxis of symptomatic COVID-19 and may mitigate the severity of COVID-19 infection.…”
Section: Covid-19: Elementsmentioning
confidence: 99%